Enhanced adsorption of Cu(ii) ions on chitosan microspheres functionalized with polyethylenimine-conjugated poly(glycidyl methacrylate) brushes. Issue 81 (17th August 2016) - Lv, Li; Zhang, Jing; Yuan, Shaojun; Huang, Liqiang; Tang, Shengwei; Liang, Bin; Pehkonen, Simo O.
Abstract : Crosslinked chitosan microspheres were tethered with branched polyethylenimine-conjugated poly(glycidyl methacrylate) brushes via surface-initiated ATRP and were further utilized as novel adsorbent to purify Cu(ii )-contaminated aqueous solution​. Abstract : To enhance the adsorption capacity of crosslinked chitosan (CCS) microspheres towards Cu(ii ) ions, well-defined poly(glycidyl methacrylate) (PGMA) brushes were grafted onto the surfaces of CCS microspheres via surface-initiated atom transfer radical polymerization (ATRP) for subsequent conjugation of polyethylenimine (PEI). The resultant PEI-grafted CCS (defined as CCS- g -PGMA- c -PEI) microsphere was used as an effective adsorbent to uptake Cu(ii ) ions from aqueous solution. Success in each functionalization step was ascertained by ATR-FTIR, XPS, SEM and water contact angle measurements. Batch adsorption experiments were performed to determine adsorption kinetics, adsorption isotherms and thermodynamics of Cu(ii ) ions on the CCS- g -PGMA- c -PEI microspheres. The adsorption equilibrium of Cu(ii ) ions on the microspheres was found to be rapidly established within 60 min at an optimal solution pH of 5.0, and the adsorption kinetics was well represented by the pseudo-second-order model, together with a significant effect of mass transfer on the Cu(ii ) adsorption rate. The Langmuir-fitted maximum adsorption capacity was about 3.58 mmol g −1 (229 mg g −1 ), and the calculated thermodynamic parameters demonstrated an endothermic and spontaneous adsorption process of Cu(ii ) ions. The PEI-grafted CCS microspheres also exhibited good regenerability and stability for recycle applications. The postulated adsorption mechanism was proposed to account for the adsorption process of Cu(ii ) ions on the CCS- g -PGMA- c -PEI microspheres.